Development, validation, and reliability of the Chrononutrition Profile Questionnaire-Pregnancy (CPQ-P) - Kok, Ee Yin; Kaur, Satvinder; Mohd Shukri, Nurul Husna; Abdul Razak, Nurliyana; Takahashi, Masaki (BioMed Central, 2024)
Background During pregnancy, physiological changes can affect eating and sleeping habits, which may eventually have negative consequences for maternal and foetal health. To better understand these changes, it is essential to develop a reliable questionnaire that addresses lifestyle habits such as snacking and daytime napping. This study aimed to determine the validity and reliability of the Chrononutrition Profile Questionnaire-Pregnancy (CPQ-P).